Info Sim: Prototyping an information system for Digital Factory management. (December 2015) - Ayadi, Mohamed; Affonso, Roberta Costa; Cheutet, Vincent; Haddar, Mohamed
Digital Factory can be defined as a set of software tools and methodologies allowing the design, simulation, initiation and optimization of production systems, with regard to the product development process. However, it remains not widespread in the industries, essentially due to the insufficient capability to communicate between the different entities and actors implied in the product development process and so to ensure a global consistency of the product and its production system definition. In this research work, we propose an information system dedicated to the management of data and information of product, production and simulation, which allows the integration of different points of view and the communication between different actors who participate in the Digital Factory process. Such information system has been tested on a case study coming from an industrial context.